Synthesis, physical and chemical properties of 2-((4-R-3-(morfolinomethylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts - R. О. Shcherbyna (Zaporozhye State Medical University, 2017)
Today's medicine and pharmacy undoubtedly need new and effective drugs. The 1,2,4-triazole derivatives occupy a special place among the wide variety of active organic compounds. This interest is caused primarily by high biological activity of these derivatives, low toxicity and high accessibility in terms of synthesis. Thus, drugs from 1,2,4-triazoles are known and are used extensively in medicine. It is important that a sufficiently large number of scientists-synthetics are paying attention on the heterocyclic system. Although a huge amount of information in the scientific literature is devoted to the 1,2,4-triazole derivatives, the 2-((4-R-3-(morfolinometylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts are virtually unexplored. The purpose of the work. Synthesis and establishing of the physical and chemical parameters of new 2-((4-R-3-(morfolinometylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid salts. Materials and methods. The study of physical and chemical properties of the obtained compounds was conducted by the methods that are listed in the State Pharmacopoeia of Ukraine 2.0. The melting point was defined on the device which determines the melting point MPA100. The elemental composition of the compounds was found on the analyzer Elementar Vario ЕL cube (CHNS) . 1H NMR specters of obtained compounds were recorded by using a spectrometer Varian Mercury VX-200 (1H, 200 MHz) and decrypted by a computer program SpinWorks 3.1.8. Chromatography-mass spectral studies were conducted on the gas-liquid chromatograph Agilent 1260 Infinity HPLC equipped with a mass spectrometer Agilent 6120 (ionization in electrospray (ESI)). Results and discussion. As the source (starting) compounds 2-((4-R-3-(morfolinometylen)-4H-1,2,4-triazole-5-yl)thio)acetic acids (where, R = H, CH3, C2H5, C6H5, NH2) were taken. Further, by the action of ammonia hydroxide, sodium and potassium hidrogen carbonates, piperidine, morpholine, methylamine, monoethanolamine and tributylamine in alcohol or aqueous media the corresponding salts were obtained. Conclusions. In this study were synthesized 20 new compounds, salts of 2-((4-R-3-(morfolinometylen)-4H-1,2,4-triazole-5-yl)thio)acetic acid. The structure of the synthesized compounds in all cases was confirmed by modern instrumental methods of analysis (1Н NMR-spectroscopy, chromatography-mass spectrometry and elemental analysis). The synthesized compounds can be used in further biological studies.